Astronomy, Latinity, Enlightenment: Niels Krog Bredal's Poems Commemorating the Transits of Venus, 1761 and 1769. Issue 1 (1st January 2016) - Aspaas, Per Pippin
Abstract : The subject of this article is three pieces of elegiac Latin poetry, written in Trondheim by the mayor of the town, Niels Krog Bredal. The occasion for the poems were the transits of Venus occurring in the years 1761 and 1769, a rare phenomenon attracting considerable attention from natural philosophers of the Enlightenment and spurring numerous scientific expeditions across the globe. Bredal wrote the poems to commemorate expeditions undertaken by Thomas Bugge and Urban Bruun Aaskow (Trondheim, 1761), Christian Gottlieb Kratzenstein (Trondheim, 1769), and Maximilianus Hell (Vardø, 1769). Bredal is primarily remembered as an important, albeit controversial, figure within Dano-Norwegian theatre history. His Latin poems reveal another side of his character, a person with a keen interest in the natural sciences, and more than willing to express his insights through poetry. The article includes an edition with critical apparatus, translation, and commentary.